Dr. P K Sen- the Bengali Surgeon of the Century (Cardiovascular Journal, 2011)
Dr Parafulla Kumar Sen, popularly known as P K Sen was a great Bengali surgeon of Twentieth century. Regarded as the founder of cardiothoracic surgery in India, Dr Sen performed the first intracardiac operation of any kind, the first open heart surgery and also the first heart transplantation in this subcontinent. He also made very significant contribution in the development of transmyocardial revascularization, a new technique for aortic arch replacement and described a group of nonspecific vasculitis. Dr P K Sen was born in Kolkata, the then capital of undivided Bengal in 1915. But he is little known in Bangladesh. This article is an attempt to notify the deeds of this Bengali surgeon.DOI: http://dx.doi.org/10.3329/cardio.v3i2.9200  Cardiovasc. J. 2011; 3(2): 254-257